2010
DOI: 10.1016/j.icheatmasstransfer.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in divided trapezoidal cavities filled with fluid saturated porous media

Abstract: A numerical work was performed to determine the heat transfer and fluid flow due to buoyancy forces in divided trapezoidal enclosures filled with fluid saturated porous media. In the present investigation, bottom wall was non-uniformly heated while two vertical walls were insulated and the top wall was maintained at constant cold temperature. The divider had constant thermal conductivity. Flow patterns and temperature distribution were obtained by solving numerically the governing equations, using Darcy's law.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…They compared their results by using correlation of Ridouane and Campo and observed that this correlation is valid for Rayleigh numbers in the range of 10 7 and 10 9 . Some researchers investigated the laminar natural convection inside the triangular cross-section enclosure which is applicable for roof geometry at different constant temperatures or constant heat flux boundary conditions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They compared their results by using correlation of Ridouane and Campo and observed that this correlation is valid for Rayleigh numbers in the range of 10 7 and 10 9 . Some researchers investigated the laminar natural convection inside the triangular cross-section enclosure which is applicable for roof geometry at different constant temperatures or constant heat flux boundary conditions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They studied the effects of inclination angles of the upper surface as well as the effect of the Rayleigh number, the Prandtl number, and the baffle height on the fluid flow and heat transfer. Varol [9] performed a numerical study of natural convection in divided trapezoidal enclosures filled with fluid saturated porous media. He has noted that that the conduction mode of heat transfer became dominant for higher thickness of the partition, low thermal conductivity ratio and low Rayleigh numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have also been carried out to study the convective heat transfer in the fluid saturated porous media due to its applicability in major industrial applications involving the geothermal fields [17] , bioengineering [18] , phase change process [19,20] , heat exchanger applications [21,22] , etc. A number of studies on natural convection in the porous cavities with various geometrical shapes (square, rectangular, trapezoidal, inclined, rhombic) were carried out by earlier researchers [23][24][25][26][27][28][29][30][31][32][33] . The trapezoidal cavities are highly useful in various applications and a number of research works are presented in the literature based on the practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A number of earlier studies for the flow of fluid within the porous trapezoidal enclosures were based on the first law of thermodynamics [24,29,30,46] and the thermal efficiency for such systems was not addressed using the second law of Thermodynamics. Based on the second law of Thermodynamics, every thermal process is inherently irreversible and some amount of the useful or available energy (called exergy) is destroyed during the course of the process.…”
Section: Introductionmentioning
confidence: 99%